2015
DOI: 10.1007/s10578-015-0579-2
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perceptions of Novel Treatments for Child and Adolescent Specific Phobia and Anxiety Disorders

Abstract: This study aimed to examine parents' perceptions of established treatments, including cognitive behaviour therapy (CBT) and selective serotonin reuptake inhibitors (SSRIs), relative to novel treatments of D-cycloserine (DCS) and attention bias modification (ABM) augmented CBT to determine if novel treatments are perceived as more or less favorable than established treatments. Participants included parents of children with a specific phobia, enrolled in one of two randomized controlled trials of either one-sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…More speculatively, yet consistent with Lazaratou et al (2007), these results suggest providing parents with knowledge about DCS, including information about its acute administration and minimal side-effect profile, may reduce unrealistic concerns and increase its acceptability. For example, Roberts et al (2016) found parents did not view DCS as a favourable intervention relative to psychological treatments; however, once they had been informed of the potential risks and benefits, there was a significant increase in acceptability. In these cases, good information may increase treatment acceptability by: (1) dispelling misconceptions about risks regarding DCS, and (2) highlighting the potential benefits of the intervention for their child.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More speculatively, yet consistent with Lazaratou et al (2007), these results suggest providing parents with knowledge about DCS, including information about its acute administration and minimal side-effect profile, may reduce unrealistic concerns and increase its acceptability. For example, Roberts et al (2016) found parents did not view DCS as a favourable intervention relative to psychological treatments; however, once they had been informed of the potential risks and benefits, there was a significant increase in acceptability. In these cases, good information may increase treatment acceptability by: (1) dispelling misconceptions about risks regarding DCS, and (2) highlighting the potential benefits of the intervention for their child.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Roberts, Farrell, Waters, Oar, and Ollendick (2016) compared parent perceptions of treatments for children enrolled in exposure therapy for a specific phobia augmented by either DCS or attention bias modification (novel interventions) versus cognitive behaviour therapy (CBT) and selective serotonin reuptake inhibitors (SSRIs; standard treatments). Overall, parents favoured CBT and psychological over pharmacological treatments.…”
mentioning
confidence: 99%
“…Another important aspect of DCS implementation in children is the involvement of parents in treatment-related decisions. Despite minimal risks for side effects, studies have shown that parents are generally not in favor of the use of DCS (Roberts, Farrell, Waters, Oar, & Ollendick, 2016). It is essential, however, that parents feel confident about treatment in order to successfully implement DCS.…”
Section: Target Populationsmentioning
confidence: 99%
“…[ 1 ] Cognitive behavioral therapy and selective serotonin uptake inhibitors occupy an important place in the treatment of specific phobias. [ 2 , 3 ] To the best of our knowledge, only one case of wind phobia has to date been reported in children and adolescents. [ 4 ] This case report describes a six-year-old boy with wind phobia treated with cognitive behavioral therapy and escitalopram.…”
mentioning
confidence: 99%